2015
DOI: 10.1016/j.meegid.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel hantavirus identified in black-bearded tomb bats, China

Abstract: Hantaviruses cause life-threatening diseases in human worldwide. Rodents, insectivores and bats are known hantaviral reservoirs, but lack of complete genomic sequences of bat-borne hantaviruses impedes phylogenetic and evolutionary comparison with those of rodents and insectivores. Here, a novel bat-borne hantavirus, Laibin virus (LBV), has been identified in a black-bearded tomb bat in China. The complete genomic sequence shows that LBV is only distantly related to all previously known bat-borne hantaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
1
32
1
Order By: Relevance
“…Hantaviruses (genus Hantavirus, family Bunyaviridae) are responsible for life-threatening human diseases: hantavirus cardiopulmonary syndrome (HCPS) in the Americas and hemorrhagic fever with renal syndrome (HFRS) in Asia and Europe (Krüger et al, 2011). Rodents are natural reservoirs of hantaviruses; however, recent studies have demonstrated that insectivores and bats also represent hosts for divergent hantaviruses (Xu et al, 2015;Zhang, 2014;Witkowski et al, 2016). Bats are considered the natural reservoir of a large variety of zoonotic viruses causing serious human diseases, such as lyssaviruses, henipaviruses, severe acute respiratory syndrome coronavirus, and Ebola virus (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hantaviruses (genus Hantavirus, family Bunyaviridae) are responsible for life-threatening human diseases: hantavirus cardiopulmonary syndrome (HCPS) in the Americas and hemorrhagic fever with renal syndrome (HFRS) in Asia and Europe (Krüger et al, 2011). Rodents are natural reservoirs of hantaviruses; however, recent studies have demonstrated that insectivores and bats also represent hosts for divergent hantaviruses (Xu et al, 2015;Zhang, 2014;Witkowski et al, 2016). Bats are considered the natural reservoir of a large variety of zoonotic viruses causing serious human diseases, such as lyssaviruses, henipaviruses, severe acute respiratory syndrome coronavirus, and Ebola virus (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bats are considered the natural reservoir of a large variety of zoonotic viruses causing serious human diseases, such as lyssaviruses, henipaviruses, severe acute respiratory syndrome coronavirus, and Ebola virus (Li et al, 2010). Genetically divergent bat-borne hantaviruses have been identified in Africa -Mouyassue virus (MOYV) in Cote d'Ivoire (Sumibcay et al, 2012), Magboi virus (MGBV) in Sierra Leone (Weiss et al, 2012), and Makokou virus (MAKV) in Gabon (Witkowski et al, 2016) and in Asia -Xuan Son virus (XSV) in Vietnam (Arai et al, 2013), Huangpi virus (HUPV), Longquan virus (LQUV), Laibin virus (LBV) in China (Xu et al, 2015;Guo et al, 2013), and Quezon virus (QZNV) in the Philippines (Arai et al, 2016). Here we report the detection of a novel hantavirus, tentatively named Brno virus (BRNV), in the European insectivorous bat species Nyctalus noctula collected in the Czech Republic, Central Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of SARS in 2003, interest in bat‐borne viruses has been increasing and novel viruses are continually found in bats all around the world. A number of studies reported that bats, especially from southern China, carried a variety of viruses (Chu, Poon, Guan, & Peiris, ; Ge et al., , , ; Hu et al., ; Li et al., ; Wu et al., ; Xu et al., ; Yang et al., ; Yuan et al., ). However, so far, few studies have been conducted on bats in northern China, which harbours a diversity of endemic insectivorous bats.…”
Section: Introductionmentioning
confidence: 99%
“…HFRS is a typical rodent-borne disease and a severe public health issue in China [5]. In addition to rodents, hantaviruses have recently been detected in shrews (order Soricomorpha, family Soricidae and Talpidae) [6][7][8][9][10][11] and bats (order Chiroptera, family Rhinolophidae, Hipposideridae, Vespertilionidae, and Nycteridae) [12][13][14][15][16], but it is not clear whether these hantaviruses lead to human illness. It is believed that only hantaviruses in rodent hosts (order Rodentia, family or subfamily Muridae, Arvicolinae, and Sigmodontinae) cause HFRS and HPS in Asia, Europe, Africa, and North America [17].…”
Section: Introductionmentioning
confidence: 99%